Hypertension In Pregnancy With Serum Electrolyte Disorders At The End Of Pregnancy - Anida Izatul Islami; Nita Adhani Pasundani; Mutiara Solechah (Sean Institute, 2025)
Electrolyte disorders such as sodium, potassium, and calcium are often associated with hypertension in pregnancy, especially in the late trimester. This study aims to evaluate the relationship between electrolyte levels that deviate from normal and pregnancy hypertension. Using a hospital-based cross-sectional design, the study involved 42 pregnant women with a minimum gestational age of 37 weeks who underwent antenatal care at the hospital. Blood pressure measurements and serum electrolyte analysis were performed at the same visit. The data showed that 59.5% of respondents experienced gestational hypertension, with an abnormal prevalence of sodium and potassium levels associated with hypertension. The analysis showed no ions showed a statistically significant association with hypertension in pregnancy. In retrospect, women with hypokaloids had a 1.921 times higher chance of developing hypertension in pregnancy compared to women with normocalium (OR = 1.921[0.441-8.365], p value = 0.385), while women with hyperchloride had a 2.515 times lower chance of developing hypertension in pregnancy compared to women with normocchloride (OR = 2.515 [0.544-11.632], p value = 0.238). These findings emphasize the importance of close monitoring of electrolytes in pregnant women at risk of hypertension to prevent complications.